REVOLUTION AND THE PEDAGOGY OF THE POSSESSED IN NEI LOPES’S NOVEL OIOBOMÉ - Maddox, John (Communitas, 2019)
Abstract: Nei Lopes (b. 1942, Irajá, Rio de Janeiro) is much more than a sambista[1]. In fact, he is a multifaceted Afro-Diasporic thinker and novelist who has created texts that educate Brazilians about black history. The following article provides a bio-bibliography of Lopes and an analysis of how his novel Oiobomé: A epopeia de uma nação (2010) represents what I call a “Pedagogy of the Possessed,” an Afrocentrism with similarities to Paulo Freire classic book Pedagogy of the Oppressed (1968). The novel proposes a “pedagogy of the possessed” to reimagine the course of Brazilian history, rooting it much less in European ideas and much more in quilombos, religious traditions that include possessions of the faithful and other Afro-diasporic forms of creativity and resistance. Palmares and the Haitian and Cuban Revolutions inspire Lopes. This novel is particularly important in Brazil, the country with the Americas’ largest black population (GATES, 2011). A REVOLUÇÃO E A PEDAGOGIA DO POSSUÍDO NO ROMANCE OIOBOMÉ DE NEI LOPES Resumo: Nei Lopes (b. 1942, Irajá, Rio de Janeiro) é muito mais do que um sambista. De fato, é um pensador afrocêntrico com muitos interesses, um romancista e um autor de textos que educam o povo brasileiro sobre a história negra. O presente ensaio proporciona um resumo bio-bibliográfico do autor e uma análise de como seu romance Oiobomé: A epopeia de uma nação (2010) representa o que pode considerar-se uma “pedagogia do possuído”, um afrocentrismo com semelhanças com o livro clássico de Paulo Freire, Pedagogia do oprimido (1968). O romance propõe uma “pedagogia do possuído” para reimaginar o concurso da história brasileira, baseando-a menos em ideias europeias e muito mais em quilombos, tradições religiosas que incluem a possessão dos crentes e outras formas de criatividade e resistência afro-diaspóricas. Lopes se inspira em Palmares e as Revoluções Haitiana Cubana. Esse romance é particularmente importante para o país com a maior população negra das Américas (GATES, 2011). LA REVOLUCIÓN Y LA PEDAGOGÍA DEL POSEÍDO EN LA NOVELA OIOBOMÉ DE NEI LOPES Resumen: Nei Lopes (b. 1942, Irajá, Rio de Janeiro) es mucho más que un sambista. De hecho, es un pensador afrocéntrico con muchos intereses, un novelista y un autor de textos que educan al pueblo brasileño sobre la historia negra. El presente ensayo proporciona un resumen bio-bibliográfico del autor y un análisis de cómo su novela Oiobomé: La epopeya de una nación (2010) representa lo que puede considerarse una "pedagogía del poseído", un afrocentrismo con semejanzas con el libro clásico de Paulo Freire, Pedagogía del oprimido (1968). La novela propone una "pedagogía del poseído" para reimaginar el concurso de la historia brasileña, basándola menos en ideas europeas y mucho más en quilombos, tradiciones religiosas que incluyen la posesión de los creyentes y otras formas de creatividad y resistencia afro-diaspóricas. Lopes se inspira en Palmares y las Revoluciones Haitiana Cubana. Esta novela es particularmente importante para el país con la mayor población negra de las Américas (GATES, 2011). [1] A previous version of this article appeared in Afro-Hispanic Review, Vanderbilt University, n. 36.1, p. 142-159.